GAMBARAN TINGKAT STRES AKADEMIK PADA MAHASISWA PRASEJAHTERA DALAM MENYELESAIKAN TUGAS AKHIR DITINJAU DARI JENIS KELAMIN - Zadrian Ardi; Nilma Zola; Soeci Izzati Adlya; Nadiya Rahmatika Delfri; Frischa Meivilona Yendi (LPPM Universitas Ekasakti, 2024)
This research is motivated by the phenomenon of many final-semester students not graduating on time. Academic stress is commonly experienced by students during the completion of their final projects due to both external pressures and internal self-expectations. Gender is one of the factors influencing academic stress. The sample consisted of 338 students from Universitas Negeri Padang who received the KIP scholarship in 2020, selected using Proportional Random Sampling technique. The research instrument was a questionnaire on academic stress. Data were analyzed using descriptive statistical techniques and t-test analysis. The results indicate: 1) The level of academic stress among students in completing their final projects is categorized as moderate; 2) The level of academic stress in the aspect of academic stressors is also categorized as moderate; 3) The level of academic stress regarding reactions to academic stressors is categorized as moderate; and 4) The hypothesis is accepted, indicating a significant difference in academic stress between male and female students. To help address the issues of academic stress among students, counseling services that can be provided include informational services, individual counseling, and group counseling.